Effect of Polyclonal, Monoclonal, and Recombinant (Single-Chain Variable Fragment) Antibodies on In Vitro Morphology, Growth, and Metabolism of the Phytopathogenic Mollicute Spiroplasma citri - Malembic, Sylvie (American Society for Microbiology, 2002)
Antibodies are known to affect the morphology, growth, and metabolism of mollicutes and thus may serve as candidate molecules for a plantibody-based control strategy for plant-pathogenic spiroplasmas and phytoplasmas. Recombinant single-chain variable fragment (scFv) antibodies are easy to engineer and express in plants, but their inhibitory effects on mollicutes have never been evaluated and compared with those of polyclonal and monoclonal antibodies. We describe the morphology, growth, and glucose metabolism of Spiroplasma citri in the presence of polyclonal, monoclonal, and recombinant antibodies directed against the immunodominant membrane protein spiralin. We showed that the scFv antibodies had no effect on S. citri glucose metabolism but were as efficient as polyclonal antibodies in inhibiting S. citri growth in liquid medium. Inhibition of motility was also observed.